The effects of catechins on related risk factors with Type 2 diabetes: a review - Alipour, Meysam; Malihi, Reza; Hosseini, Seyed Ahmad; Abbasnezhad, Amir; Ghavami, Abed; Shahmohammadi, Hedayat Allah; Ghanavati, Matin (Progress in Nutrition, 2018)
Insulin resistance in patients with diabetes mellitus causes complications such as cardiovascular and renal diseases. Studies have shown that catechins can be effective in controlling hyperglycemia and preventing the complications of diabetes by improving insulin sensitivity and reducing the risk factors for Type 2 Diabetes Mellitus such as oxidative stress, dyslipidemia and obesity. The aim of the present study is a review of the studies conducted in the field of the effect of catechins on the improvement of the risk factors associated with Type 2 Diabetes Mellitus. This review study was conducted by searching in the databases of Science Direct, Scopus, PubMed and using the keywords, such as catechins, green tea, insulin resistance, diabetes mellitus, hyperglycemia, obesity, dyslipidemia and oxidative stress. In this study, articles published between the years 2000-2016, were used. The results of the review of the studies showed that the catechins and food containing them can improve hyperglycemia, oxidative stress, dyslipidemia and obesity in patients with Type 2 Diabetes Mellitus.